Kelayakan Masker Tradisional Biji Pepaya Dan Ketan Hitam Untuk Perawatan Kulit Wajah Kering - Azzahra Sairi, Fathya; Laila Putri, Tiara; Rosalina, Linda; Saputra, Indra; Guzeynova, Monica Zabrina (Jurnal Tata Rias, 2024)
Skin problems, especially on the face, are often considered to diminish appearance and require significant expense. However, caring for the face with natural ingredients is safer because they are free of chemicals. The natural ingredient in question is papaya seeds, which contain the enzyme papain, which can prevent wrinkles, minimize pores, and moisturize the skin. Besides being a food ingredient, black sticky rice can also benefit skin beauty by slowing premature aging, thanks to its high antioxidant and anthocyanin content, vitamin E, and fiber. This study aims to determine the physical properties of papaya seed and black sticky rice masks, including color, aroma, texture, and panelist preferences. This is an experimental study with papaya seed and black sticky rice masks as the subjects. This quantitative study used experimental methods. Data collection methods included observation and panelist preferences for color, aroma, texture, and adhesive power. Two cosmetology and beauty lecturers, along with 10 female students from the University of North Sumatra (UNP), studied the color, aroma, texture, and adhesiveness of the masks. The results of the study showed that using a papaya seed and black sticky rice mask effectively treated dry skin. The skin exhibited a gray color from the mixture of papaya seed powder and black sticky rice, a fragrant and pleasant aroma, a very smooth texture, and good elasticity, feeling firm and supple.